2012
DOI: 10.1021/ac3023907
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intracellular Growth of Gold Nanostructures Assisted by Functionalized Graphene Oxide and Its Application for Surface-Enhanced Raman Spectroscopy

Abstract: Hybridization of metal nanoparticles with graphene oxide for high performance surface-enhanced Raman scattering (SERS) has attracted overwhelming attention in recent years. Herein, a one-pot green route for intracellular synthesis of gold nanostructures assisted by poly(vinylpyrrolidone) (PVP)-functionalized graphene oxide (GO) was proposed. The hybrids obtained [GO/PVP/intracellularly grown gold nanoparticles (IGAuNs)] randomly scattered throughout the cell. Compared with the IGAuNs, the growth of GO/PVP/IGAu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 43 publications
2
58
0
Order By: Relevance
“…Another group of scientists, reported a one-pot green technique for the intracellular synthesis of AuNS aided by poly(vinylpyrrolidone) (PVP)-functionalized GO [220]. The random intracellular distribution of GO/PVP/IGAuNPs in the cells allowed for ultrasensitive detection of cellular components of cancer cells (A549, 4T1, and HeLa cells) located in the cytoplasm, nucleoplasm, and nucleolus using SERS (Figure 13) and signals induced by the hybrid composites could be collected as early as 15 h, thus enabling the early detection or diagnosis of cancer as well.…”
Section: Graphene–gold Nanoparticle Hybrid For Biosensing and Bioimentioning
confidence: 99%
See 2 more Smart Citations
“…Another group of scientists, reported a one-pot green technique for the intracellular synthesis of AuNS aided by poly(vinylpyrrolidone) (PVP)-functionalized GO [220]. The random intracellular distribution of GO/PVP/IGAuNPs in the cells allowed for ultrasensitive detection of cellular components of cancer cells (A549, 4T1, and HeLa cells) located in the cytoplasm, nucleoplasm, and nucleolus using SERS (Figure 13) and signals induced by the hybrid composites could be collected as early as 15 h, thus enabling the early detection or diagnosis of cancer as well.…”
Section: Graphene–gold Nanoparticle Hybrid For Biosensing and Bioimentioning
confidence: 99%
“…The random intracellular distribution of GO/PVP/IGAuNPs in the cells allowed for ultrasensitive detection of cellular components of cancer cells (A549, 4T1, and HeLa cells) located in the cytoplasm, nucleoplasm, and nucleolus using SERS (Figure 13) and signals induced by the hybrid composites could be collected as early as 15 h, thus enabling the early detection or diagnosis of cancer as well. Specifically, a comparison of the SERS spectral analysis of GO/PVP/IGAuNPs and IGAuNPs individually showed that the hybrid structure results in five times larger Raman enhancement, possibly due to the formation of IGAuNP aggregates on GO [220]. More recently, Nergiz et al [219] demonstrated a novel class of multifunctional hybrid nanopatches made up of GO and Au nanostars and the internalization of intact nanopatches into human epithelial breast cancer cells (SKBR-3) by Raman imaging.…”
Section: Graphene–gold Nanoparticle Hybrid For Biosensing and Bioimentioning
confidence: 99%
See 1 more Smart Citation
“…Guo et al recently reported an intracellularly produced gold nanoparticle modified by poly(vinylpyrrolidone) (PVP)-functionalized graphene oxide (GO) which was named as PVP/GO/IGAuNs. 109 The distribution of PVP/GO/IGAuNs in cells then allowed for the sensitive monitoring of intracellular chemical compositions including the cytoplasm, nucleoplasm, and even the nucleus using SERS. Moreover, Yang et al also reported GO–Ag nanoparticles, which enabled very rapid cancer cell probing and imaging with a detection time of 0.06 s per pixel.…”
Section: Graphene–nanoparticle Hybrid Materials For Sensing Applicmentioning
confidence: 99%
“…Materials derived from biological systems such as plant extracts, microorganisms, and eukaryotic cells have proven to be effective and feasible bioreductive agents for the green synthesis of Ag nanoparticles (AgNPs), gold nanoparticles, and iron nanoparticles [10,11,12,13,14,15,16,17,18,19]. Melanogenesis begins with l -dihydroxyphenylalanine ( l -DOPA) acquired from the hydroxylation of l -tyrosine, and is followed by a series of redox polymerization reactions [20].…”
Section: Introductionmentioning
confidence: 99%